MiR-146a alleviates acute lung injury via inhibiting Notch 1 signaling pathway targeting macrophage: MiR-146a alleviates acute lung injury - Zhao, Qiumin; Wang, Yan; Zou, Jing; Kuang, Rong; Ji, Shiyan (Cellular and Molecular Biology, 2024)
Acute lung injury (ALI) is associated with the leukocyte infiltration and inflammation. Previous studies have shown that miR-146a is a valid regulator of the macrophage polarization in vitro inflammatory model. However, it is unclear whether miR-146a plays a protective role in ALI via modulating macrophage inflammation. To explore the potential therapeutic effect mechanism of miR-146a on ALI. We analyzed the expression of miR-146a in acute injured lung tissues and differentiated macrophage. Lipopolysaccharide (LPS) and interleukin-4 (IL-4) were employed in provoking the macrophage to polarization. We used miR-146a mimics to improve the overexpression of miR-146a and investigated the effect of increased miR-146a on LPS-induced ALI mice via the target of macrophage polarization. We showed that the expression of miR-146a markedly decreased in injured lung tissue and type M1 macrophage, while increased miR-146a expression exhibited in type M2 macrophage. Moreover, overexpression of miR-146a in LPS-induced macrophage reversed inflammatory M1 phenotype to anti-inflammatory M2 phenotype and mitigated inflammatory level via inhibiting Notch 1 signaling pathway. Hence, inflammation, infiltration, integrity of capillary barrier, and histology in ALI model were corrected after miR-146a overexpression treatment. These results suggested that miR-146a promotes type M2 macrophage polarization via restraining Notch 1 signaling pathway. Overexpression of miR-146a prevents inflammation damage and ameliorates lung damage after LPS induction. Therefore, miR-146a may serve as a promising target for the therapy of ALI in the future.